2010
DOI: 10.1242/jeb.042705
|View full text |Cite
|
Sign up to set email alerts
|

Tarsal taste neuron activity and proboscis extension reflex in response to sugars and amino acids in Helicoverpa armigera (Hübner)

Abstract: SUMMARYIn adult female Helicoverpa armigera (Hübner), the fifth tarsomere of the prothoracic legs bears 14 gustatory trichoid chemosensilla. These chemosensilla were characterized through electrophysiological experiments by stimulating with sucrose, glucose, fructose, maltose, myo-inositol and 20 common amino acids. In electrophysiological recordings from nine sensilla, responses were obtained to certain compounds tested at 100mmoll -1 , and the response spectra differed from broad to narrow. The four sugars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 45 publications
6
49
0
Order By: Relevance
“…a similar morphology was observed in Bactrocera where it was related to detection of chemical substances and odours (Zhang et al 2012). As concerns chemosensilla, in Helicoverpa armigera, Zhang et al (2010) reported that the fifth tarsomere showed two clusters of 14 TS. In Rhagoletis pomonella, another Tephritidae, Crnjar and Prokopy (1982) identified three (B, C and D) of the four types of tarsal sensilla proposed by Grabowski and Dethier (1954).…”
Section: Morphologysupporting
confidence: 58%
“…a similar morphology was observed in Bactrocera where it was related to detection of chemical substances and odours (Zhang et al 2012). As concerns chemosensilla, in Helicoverpa armigera, Zhang et al (2010) reported that the fifth tarsomere showed two clusters of 14 TS. In Rhagoletis pomonella, another Tephritidae, Crnjar and Prokopy (1982) identified three (B, C and D) of the four types of tarsal sensilla proposed by Grabowski and Dethier (1954).…”
Section: Morphologysupporting
confidence: 58%
“…However, we do not know which compounds are actually used for discrimination. Insects are generally able to perceive tastes similar to humans and have receptors for bitter and sweet substances as well as for several amino acids (Zhang et al, 2010;Toshima and Tanimura, 2012; for bees, see Linander et al, 2012), glycerol and water (as reviewed for Drosophila by Liman et al, 2014). Bees are even able to sense very small amounts of sugar (de Brito Sanchez, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in blood-feeding tsetse flies identified neurons in tarsal taste hairs that are exquisitely sensitive to several individual amino acids, as well as to a mixture of amino acids that are found in human sweat (van der Goes van Naters and den Otter, 1998). Amino acid-sensing neurons have also been described in cabbage butterflies (Van Loon and Van Eeuwijk, 1989) and Helicoverpa moths (Zhang et al, 2011; Zhang et al, 2010). …”
Section: Introductionmentioning
confidence: 99%